2015
DOI: 10.1007/s11104-015-2443-3
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium impairs iron homeostasis in Arabidopsis thaliana by increasing the polysaccharide contents and the iron-binding capacity of root cell walls

Abstract: Background and aims Iron (Fe) deficiency is a wellknown symptom of cadmium (Cd) toxicity. Here, the mechanisms underlying Cd impairment of Fe homeostasis in Arabidopsis were investigated. Methods Arabidopsis plants were subjected to 0 (CK) or 10 μM Cd treatments. After the treatments period, Fe concentrations, expression levels of Fe uptake-and translocation-related genes, polysaccharide concentrations, pectin methylesterase activities (PME) and the degree of pectin methylation (DM) were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…One possible mechanism underlying these disturbances is cell wall remodeling. In a study using A. thaliana , leaf chlorosis was observed after Cd exposure mainly as a result of Cd-induced Fe deficiency in the shoots ( Xu et al, 2015 ). Upon Cd exposure, the pectin and hemicellulose content of the root cell walls increased, leading to a major retention of Fe in the roots and hence a decrease of the Fe concentration in the shoots.…”
Section: Cadmium Impairs Proper Nutrient Homeostasismentioning
confidence: 99%
“…One possible mechanism underlying these disturbances is cell wall remodeling. In a study using A. thaliana , leaf chlorosis was observed after Cd exposure mainly as a result of Cd-induced Fe deficiency in the shoots ( Xu et al, 2015 ). Upon Cd exposure, the pectin and hemicellulose content of the root cell walls increased, leading to a major retention of Fe in the roots and hence a decrease of the Fe concentration in the shoots.…”
Section: Cadmium Impairs Proper Nutrient Homeostasismentioning
confidence: 99%
“…The endogenous levels of NO in roots were visualized using the fluorescent probe diaminofluorescein-FM diacetate (DAF-FM DA) and epifluorescence microscopy ( Sun et al , 2014 ; Xu et al , 2015 ). Briefly, root tips (0–10mm) were loaded with 10 μM DAF-FM DA in 20mM HEPES-NaOH buffer (pH 7.4) for 20min, washed three times with fresh buffer, and observed under an epifluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Iron deficiency is a well-known consequence of metal toxicity [e.g. Cd (Xu et al, 2015 )] and seems to increase ethylene sensitivity (García et al, 2010 ), which potentially affects metal-induced responses related to ethylene as well. It has been shown that nutrient stress—either a reduced or increased availability—affects ethylene biosynthesis and perception in plants via the induction of an oxidative burst (Iqbal et al, 2013a ), again highlighting the link between ethylene and ROS signaling.…”
Section: Crosstalk Between Ethylene and Other Players In The Metal Stmentioning
confidence: 99%